Women writers of the First World War : an annotated bibliography - Ouditt, Sharon, 1963- (Routledge, 2000)
'They also serve who only stand and wait' The idea of there being a 'women's writing' during the First World War is often dismissed. The war, the story goes, was a masculine domain, and as women did not fight, it is also assumed that they were excluded from a war experience. This bibliography challenges that view by listing and annotating hundreds of published books, articles, memoirs, diaries and letters written by women during the First World War. Included are: * Virginia Woolf * Katherine Mansfield * G.B Stern * Brenda Girvin * known and unknown autobiographers a.